2017
DOI: 10.1001/jamaophthalmol.2017.4152
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Stargardt Disease as Determined by Fundus Autofluorescence in the Retrospective Progression of Stargardt Disease Study (ProgStar Report No. 9)

Abstract: for the ProgStar Study Group IMPORTANCE Sensitive outcome measures for disease progression are needed for treatment trials of Stargardt disease. OBJECTIVE To describe the yearly progression rate of atrophic lesions in the retrospective Progression of Stargardt Disease study. DESIGN, SETTING, AND PARTICIPANTSA multicenter retrospective cohort study was conducted at tertiary referral centers in the United States and Europe. A total of 251 patients aged 6 years or older at baseline, harboring disease-causing vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 32 publications
6
113
2
Order By: Relevance
“…In the current study, we applied a similar blue light source and a shorter exposure time, but in the pigmented Abca4 −/− mice, which resembled similar phenotypic features of advanced Stargardt disease. Our work also indicates that the fundus AF examination in both SW‐AF and NIR‐AF provides more information for the diagnosis and evaluation of disease progression …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the current study, we applied a similar blue light source and a shorter exposure time, but in the pigmented Abca4 −/− mice, which resembled similar phenotypic features of advanced Stargardt disease. Our work also indicates that the fundus AF examination in both SW‐AF and NIR‐AF provides more information for the diagnosis and evaluation of disease progression …”
Section: Discussionmentioning
confidence: 56%
“…Our work also indicates that the fundus AF examination in both SW-AF and NIR-AF provides more information for the diagnosis and evaluation of disease progression. 32,71 Our mouse model reflects the clinical manifestations of advanced Stargardt disease and AMD. Quantitative analysis of RPE nuclei and photoreceptor nuclei indicated that blue light-induced RPE loss preceded the photoreceptor loss in Abca4 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, microperimetry is being assessed as a potentially more accurate functional outcome measure for future clinical trials [18]. In ProgStar, anatomic endpoints to assess progression of atrophy through both FAF and OCT are being assessed [19,20].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It is the most common form of inherited macular degeneration, affecting roughly in 1 in 10,000 people. The age of onset of juvenile and early adult STGD1 is usually [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] years with some cases occurring in older adults (late-adult onset STGD1) [1,2]. These patients develop irreversible vision loss due to atrophy of the macular retinal pigment epithelium (RPE) and loss of photoreceptors, with patients presenting at a younger age having worse visual outcomes compared to those with later onset [1].…”
Section: Introductionmentioning
confidence: 99%
“…The term "definitely decreased AF" (DDAF) was used for areas in which the level of darkness was close to 100% (at least 90%) in reference to the optic nerve head/blood vessels. Regions with levels between 50 and 90% darkness were defined as "questionably decreased AF" (QDAF); in these lesions, the sharpness of the corresponding lesion border defined a lesion either as "well-demarcated QDAF" or "poorly demarcated QDAF" [16][17][18][19].…”
Section: Phenotype Classificationmentioning
confidence: 99%